2010
DOI: 10.1002/anie.200906607
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Stepwise Synthesis of Functional Multijunction Molecular Wires on Gold Electrodes and Gold Nanoparticles

Abstract: Tunneling through: The sequencing of electron‐donating and electron‐accepting components that are separated by a σ‐electron bridge has resulted in the highest rectification ratio to date from a molecular diode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 36 publications
(33 reference statements)
2
32
0
Order By: Relevance
“…This clearly suggests the existence of oxidized thiolate staples on the cluster surface. The S 2p 3/2 peak, seen at 163.1 eV (Au 25 ) and 162.8 eV (red luminescent species), for both clusters supports the Au-S thiolate binding to the core 65 and confirms the existence of only one type of S. On the basis of the above results, the enhanced luminescence in Au 25 SBB 18 upon heating could be attributed to the charge transfer from the oxidized surface thiolate ligands to the core of QC through the Au-S bonds and direct donation of delocalized electrons from electron-rich ligands to the metal core, as described by Jin et al 9 The presence of the thiolate shell around the cluster surface was further verified by thermogravimetric analysis (TGA). The red-emitting Au 29 QCs showed higher organic content (observed metal to the organic content ratio (57.9% : 42.0%)), than the parent Au 25 (60.2% : 39.7%) (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…This clearly suggests the existence of oxidized thiolate staples on the cluster surface. The S 2p 3/2 peak, seen at 163.1 eV (Au 25 ) and 162.8 eV (red luminescent species), for both clusters supports the Au-S thiolate binding to the core 65 and confirms the existence of only one type of S. On the basis of the above results, the enhanced luminescence in Au 25 SBB 18 upon heating could be attributed to the charge transfer from the oxidized surface thiolate ligands to the core of QC through the Au-S bonds and direct donation of delocalized electrons from electron-rich ligands to the metal core, as described by Jin et al 9 The presence of the thiolate shell around the cluster surface was further verified by thermogravimetric analysis (TGA). The red-emitting Au 29 QCs showed higher organic content (observed metal to the organic content ratio (57.9% : 42.0%)), than the parent Au 25 (60.2% : 39.7%) (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…S2 †), which are the characteristic features of thiolate. 28 Thus, it is evident that the cluster core is stabilized by the thiol groups of the protein (predominantly from the cysteine residues, since they are highly reactive) in view of the large affinity of S to noble metals. The atomic Au : S and Ag : S ratios suggested one cluster per intact protein with excess thiol-thiolate groups.…”
Section: Resultsmentioning
confidence: 99%
“…12 iii) The reproducibility, yield, and operational lifetime of many of these systems have been low, or have not been reported. 13 iv) Other asymmetries in the junction unrelated to the molecular component -for example, electrodes of different materials, or junctions with two different types of contacts of the SAM with electrodes -may have contributed to rectification (without a molecular origin). 11,19 Cahen et al 20,21,22 showed that their Si-alkyl//Hg based junctions can give detailed information about the mechanisms of charge transport across these The junction at one bias is the reference for the junction at the opposite bias, because the value of R is determined by dividing the current in on direction of bias by the current measured at the opposite direction (eq.…”
Section: Introductionmentioning
confidence: 99%